Factors contributing to learning losses among primary school children: a scoping review - Pek, Lim Seong; Nadarajan, Na-Thinamalar Magiswari; Khusni, Hafizah; Mee, Rita Wong Mee; Ismail, Md Rosli; Adha, Nur Syafiqah Qistina Shahrel; Arma, Amin E Sama Ae Jeh (Intelektual Pustaka Media Utama, 2024)
Learning loss pertains to the decline or regression in knowledge and abilities, as well as setbacks in academic advancement. This phenomenon typically arises from prolonged interruptions or gaps in the pupil’s educational journey. Learning loss can be observed in diverse manifestations due to many factors. One example that can be illustrated is the disruption of formal education due to the COVID-19 pandemic that struck the world in 2019. As a result, this phenomenon has impacted students’ academics, whether at the school level or higher education institutions, especially primary school students, thus causing learning poverty. This scoping review aims to identify the degree of reading literacy among primary school students and to investigate the factors that contribute to the learning losses of primary school students from the reading aspect. Four databases, including Scopus, education resources information center (ERIC), bielefeld academic search engine (BASE) and directory of open access journals (DOAJ), were used in this research, which found 40 articles for eligibility. Only 20 articles are eligible for analysis and reference after the exclusion and inclusion process for data collection. The findings show that learning losses have impacted the education sector, leading to poverty, especially among primary school children.